Organic and mineral fertilization on productivity and postharvest of okra - Jonnathan Richeds da Silva Sales; Geocleber Gomes de Sousa; Raimundo Gleidison Lima Rocha; Francisco Hermeson Rodrigues Costa; Elizeu Matos da Cruz Filho; Kelly Nascimento Leite (Agro@mbiente On-line, 2020)
Mineral fertilization promotes good results for the components of production and quality of okra fruit; however, it raises the cost of production, making it, sometimes, unviable to the small producers. Thus, this study aimed to evaluate organic and mineral fertilization in different forms, in the components of production, productivity, and quality of okra fruits. The experiment was carried out, under full sunlight, in a completely randomized design (CRD), with six replications. The treatments corresponded to the different forms of fertilization, being: MF = mineral fertilization with NPK (100% of the recommended dose); BF = fertilization with bovine biofertilizer (100% of the NPK contents); VA = fertilization with vegetable ash (100% of NPK contents); MFBF = mineral fertilizer (50%) + bovine biofertilizer (50%); MFVA = mineral fertilizer (50%) + vegetable ash (50%); C = control (without fertilization). The variables analyzed were as follows: number of fruits per plant (NFP), average fruit mass (AFM), fruit length (FL), fruit diameter (FD), fruit skin thickness (FST), and yield (Y). Therefore, the use of bovine biofertilizer in isolation or supplemented with mineral fertilization enhances the production of okra and improves the quality of the fruits, reveling as promising alternatives for growing okra.